2001
DOI: 10.2486/indhealth.39.231
|View full text |Cite
|
Sign up to set email alerts
|

Toluene Alters Mu-Opioid Receptor Expression in the Rat Brainstem.

Abstract: Toluene is an ototoxic organic solvent widely used in industry and could be a cause of sleep apnea. Acute toluene administration in rats induces an increase in the number of neural cells immunostained for mu-opioid receptors in several brainstem nuclei, such as the inferior colliculus, dorsal and lateral periaqueductal gray and dorsal raphe, without changes in the superior colliculus and the interpeduncular and lateral reticular nuclei. These data suggest that mu-opioid receptors could be involved in toluene-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…According to von Euler and coworkers, 16 exposure to 80 ppm toluene 6 h/day, 5 days/week for 3 months produced an increase in mu‐opioid receptor levels in nucleus accumbens (27%), but not in caudate putamen or frontoparietal‐insular cortex in rats. In another study, Saracibar and coworkers 17 demonstrated that i.p. administration of 0.56 mg/kg toluene, once a day for 5 days, increased mu‐opioid receptor immunostaining in raphe dorsal nuclei, inferior and superior colliculus, and periaqueductal gray of rats.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…According to von Euler and coworkers, 16 exposure to 80 ppm toluene 6 h/day, 5 days/week for 3 months produced an increase in mu‐opioid receptor levels in nucleus accumbens (27%), but not in caudate putamen or frontoparietal‐insular cortex in rats. In another study, Saracibar and coworkers 17 demonstrated that i.p. administration of 0.56 mg/kg toluene, once a day for 5 days, increased mu‐opioid receptor immunostaining in raphe dorsal nuclei, inferior and superior colliculus, and periaqueductal gray of rats.…”
Section: Discussionmentioning
confidence: 95%
“…At the molecular level, several studies have found that, similarly to ethanol, 10–12 solvents potentiate GABA A receptor function 13 and act as noncompetitive NMDA receptor antagonists, among other actions 14,15 . Additionally, in vitro studies have shown that repeated solvent exposure produces changes in mu‐opioid receptor levels in diverse brain areas 16,17 . On the other hand, behavioral studies have reported that toluene and TCE increase locomotor behavior, impair motor coordination, 18 have anxiolytic‐like actions, 18,19 and increase nociception 19,20 …”
Section: Introductionmentioning
confidence: 99%
“…toluene for 6 h a day, 5 days a week over 3 months resulted in reduced [ 3 H]neurotensin binding in the orbital cortex, but increased accumbal binding of [ 3 H]etorphine to opioid receptors ( von Euler et al ., 1988 ). More recently, acute toluene exposure was shown to increase μ‐opioid receptor protein in brain stem nuclei, including the dorsal raphe and periaqueductal grey ( Saracibar et al ., 2001 ), whereas seven daily injections of toluene (600 mg kg −1 i.p.) increased dopamine and serotonin levels in rat basal ganglia ( Riegel et al ., 2004 ).…”
Section: Neuropharmacological Effects Of Inhalants: Receptor Expressimentioning
confidence: 99%
“…In rats, acute administration of toluene, a solvent with ototoxic properties, induces an increase in the number of neural cells immunostained for MOR in several brainstem nuclei including the IC. These data have been interpreted to indicate a link between opioid receptors and auditory function (Saracibar et al ., 2001).…”
Section: Introductionmentioning
confidence: 96%